RELATIONSHIPS BETWEEN HISTOPATHOLOGY TYPE AND NEOADJUVANT CHEMOTHERAPY RESPONSE IN IB2 AND IIA2 CERVICAL CANCER - Muhammad, Syamel (Universitas Andalas, 2020)
Background: Cervical cancer was the fourth common cancer in women in the world and the second most in Indonesia. Chemotherapy has been evaluated as a therapy strategies to treat stage IB2 and IIA2 cervical cancer. Neoadjuvant chemotherapy was still being a controversy for the chemotherapy resistance patient. This would delay the provision of definitive therapy. A marker is needed to identify patient which more relatively resistant to chemotherapy. Squamous Cell Carcinoma (SCC) type was known be have better response to neoadjuvant chemotherapy than non-Squamous Cell Carcinoma (nSCC) type, but there no studies at Dr.M.Djamil General Hospital yet on this matter before.Objective: To obtain the relationship between histopathology type and neoadjuvant chemotherapy response on cervical stage IB2 and IIA2 cervical canser.Method: This cohort analytic study conducted at Dr.M.Djamil Padang Hospital which obtained 35 samples of stage IB2 and IIA2 cervical cancer patients whom treated with neoadjuvant chemotherapy. Sampling was done by consecutive sampling technique. Results of histopathology and results of ultrasound examinations before and after given neoadjuvant chemotherapy were included to data. Data analysis used Chi-Square test.Results: CR + PR in the SCC and NSCC group were 32% and 50%, while SD + PD was 68% in SCC group and 50% in NSCC group.Conclusion: There was no significant relationship between histopathological type and neoadjuvant chemotherapy response to stage IB2 and IIA2 cervical cancer (p = 0.44).Keywords :histopatolgi, chemotherapy, cervical cancer